Major public transport hubs in the light rail design and operation - Romani, Fosca; Plogstert, Steffen (Proceedings from the Annual Transport Conference at Aalborg University, 2015)
Light Rail Transport systems (shortly LRT in the text) are experiencing a second youth in Europe in general and more specifically in Northern European countries in recent years. New lines are built and existing LRT networks are extended, both in countries where they previously existed (like in Denmark) or where they see the light for the first time. We see an important goal in the planning process of a LRT in conceiving and designing user friendly projects, which will attract the maximal number of customers. Only by obtaining this goal a LRT will be a successful alternative to road/private traffic and hence be the driving factor for an environmentally conscious urban development. Thus a key factor in the realization of the design and the operational concept of a high performance LRT is to guarantee rapid and trustworthy connections combined with optimized and reliable interchanges with other public transport modes. This will give the customers the feeling of a competitive transport service they will choose because of its attractiveness. The paper will analyze the role of major public transport hubs in LRT projects during the realization of the design and the operational concept: which are the main issues integrating a new LRT hub in the existing public transport network? what operational, infrastructural or systems solutions make the hub attractive? what operational challenges have to be overcome?